Role of Cooperative in Promoting Women’s Empowerment - Acharya, Chiranjivi; Kumar, Nand Kishor (Darul Yasin Al Sys, 2025)
Women empowerment is the process of enhancement of women development through different initiatives, cooperative is the unity of people, basically for economic enhancement of local people. The cooperative collects the small amount money from local people basically from women and they provide to the needy people among the members of cooperative. Main aim of this article is to analyzed the role of cooperative to enhance the women empowerment of study area, this article will be useful to researcher, students, teachers and other related people who are directly and indirectly working in cooperative and women empowerment field. Quantitative research methods, descriptive and analytical research design has been applied with deductive approach. Both primary and secondary data are used. Data are analyzed using the latest data analysis tool and technology. The cooperative is playing vital role to empowerment of women through the economic enhancement.